1986
DOI: 10.1111/j.1768-322x.1986.tb00446.x
|View full text |Cite
|
Sign up to set email alerts
|

The intracellular lumen: origin, role and implications of a cytoplasmic neostructure

Abstract: Ultrastructurally, the intracellular lumen appears as a more or less spherical cavity with osmiophilic substance, bordered with microvilli and surrounded by a filamentous network. Epithelial cancer cells, both healthy cultured and hormonally stimulated in vivo, often present such structures, which probably result from a dysfunction of the Golgi apparatus and cytoskeleton. This characterizes an abortive secretory process, which may be the consequence of a great hormonal sensitivity of the cells or of a loss of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 0 publications
2
27
0
Order By: Relevance
“…A similar phenotype is observed in Rab8-knockout mice (Sato et al, 2007), and previous work has shown evidence of interactions between Rab8 and myosin-Vb (Roland et al, 2007). Intracellular vacuoles, also called intracellular lumens (Remy, 1986) or VACs (vacuolar apical compartments) (Vega-Salas et al, 1988), are often observed in transformed epithelial cells and in epithelial cells deprived of cell-cell contacts. They are thought to be normal intermediates in the biogenesis of the apical surface in epithelial and endothelial cells, and often result from the fusion of apical-transport vesicles under conditions of reduced delivery to the apical PM (Verges et al, 2007).…”
Section: Rho Gtpases and Actin Dynamics In Apical Deliverymentioning
confidence: 56%
“…A similar phenotype is observed in Rab8-knockout mice (Sato et al, 2007), and previous work has shown evidence of interactions between Rab8 and myosin-Vb (Roland et al, 2007). Intracellular vacuoles, also called intracellular lumens (Remy, 1986) or VACs (vacuolar apical compartments) (Vega-Salas et al, 1988), are often observed in transformed epithelial cells and in epithelial cells deprived of cell-cell contacts. They are thought to be normal intermediates in the biogenesis of the apical surface in epithelial and endothelial cells, and often result from the fusion of apical-transport vesicles under conditions of reduced delivery to the apical PM (Verges et al, 2007).…”
Section: Rho Gtpases and Actin Dynamics In Apical Deliverymentioning
confidence: 56%
“…This compartment was termed "vacuolar apical compartment" or VAC (Vega-Salas et al, 1987). Similar vacuoles are found in a variety of carcinomas (Remy, 1986;Kern et al, 1987; VegaSalas et al, 1993).…”
Section: Sustained Inhibition Of Epithelial Polarity Causes Intracellmentioning
confidence: 91%
“…This compartment was termed "vacuolar apical compartment" or VAC (Vega-Salas et al, 1987). Similar vacuoles are found in a variety of carcinomas (Remy, 1986;Kern et al, 1987; VegaSalas et al, 1993).We studied the subcellular localization of plasma membrane SNAREs in MDCK cells grown under these conditions. A high percentage (Ͼ50%) of the cells display one or more large vacuolar compartments that are positive for the endogenous apical marker protein gp135 and are indistinguishable in appearance from previously described VACs (Figure 4).…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…This compartment was termed 'vacuolar apical compartment' or VAC (38). Similar vacuoles are found in a variety of carcinomas (16,31,40).…”
Section: Bodymentioning
confidence: 93%